DEVELOPING OF DIFFERENTIATED NATURAL AND SOCIAL SCIENCE LEARNING TOOLS IN MERDEKA CURRICULUM IN ELEMENTARY SCHOOLS - Ahmad Ipmawan Kharisma; A.F. Suryaning Ati MZ; Rossa Selfi Yuliana Putri (Universitas Majalengka, 2024)
One way to design and carry out a learning process based on student characteristics is with a differentiatio learning strategy. The differentiation learning strategy is a very important to implement in the 21st century. This research and development study aimed to develop a differentiated learning tool. The research subjects were fourth grade elementary school students. The 4D model with four stages (define, design, development, and dissemination) was used in this study. However, the implementation of this research was only limited to the development stage. The development of differentiated natural and social sciences learning tools aimed to produce ATP, teaching modules, teaching materials, student worksheets, and learning assessments which were valid, practical, and effective for use in elementary school students. The results indicated that ATP had a percentage of 91.5%, teaching modules with a percentage of 91%, teaching materials with a percentage of 93%, student worksheets with a percentage of 91.62%, and an assessment with a percentage of 91.12% so that the average was 91.64% with a valid category. Differentiated science and science learning tools can be used as learning tools in elementary schools with limited trial student response results of 91% and field trial student response results of 97%. So it can be concluded that the differentiated science and science learning tools developed are valid for use as learning tools in the student learning process in elementary schools.